Sodium-glucose cotransporter-2 inhibitors and incidence of atrial fibrillation in older adults with type 2 diabetes: a retrospective cohort analysis - Li, Yujia; Tang, Huilin; Guo, Yi; Shao, Hui; Kimmel, Stephen E.; Bian, Jiang; Schatz, Desmond A.; Guo, Jingchuan (Frontiers in Pharmacology, 2024)
Objectives: To investigate the risk of atrial fibrillation (AF) with sodium-glucose cotransporter-2 inhibitors (SGLT2i) compared to dipeptidyl peptidase-4 inhibitor (DPP4i) use in the elder US adults and across diverse subgroups.We conducted a retrospective cohort analysis using claims data from 15% random samples of Medicare fee-for-service beneficiaries. Patients were adults with type 2 diabetes (T2D), no preexisting AF and have newly initiated on SGLT2i or DPP4i.The outcome was the first incident AF. Inverse probability treatment weighting (IPTW) was used to balance the baseline covariates between the treatment groups including sociodemographics, comorbidities and co-medications. Cox regression models were used to assess the effect of SGLT2i versus DPP4i on incident AF.Results: Of the 97,436 eligible individuals (mean age 71.2±9.8 years, 54.6% women), 1.01% (n=983) had incident AF over a median follow-up of 361 days. The adjusted incidence rate was 8.39 (95% CI: 6.67-9.99) and 11.70 (95% CI: 10.9-12.55) per 1000 person-years in the SGLT2i group and DPP4i group, respectively. SGLT2i were associated with a significantly lower risk of incident AF (HR 0.73; 95% CI, 0.57 to 0.91; p = 0.01) than DPP4i. The risk reduction of incident AF was significant in non-Hispanic White individuals and subgroups with existing atherosclerotic cardiovascular diseases and chronic kidney disease.Conclusions: Compared to DPP4i, the use of SGLT2i was associated with a lower risk of AF in patients with T2D. Our findings contribute to the real-world evidence in the effectiveness of SGLT2i in preventing AF and support a tailored therapeutic approach to optimize treatment selection based on individual characteristics.